2023
DOI: 10.3390/ejihpe13110181
|View full text |Cite
|
Sign up to set email alerts
|

Drivers and Consequences of ChatGPT Use in Higher Education: Key Stakeholder Perspectives

Ahmed M. Hasanein,
Abu Elnasr E. Sobaih

Abstract: The incorporation of artificial intelligence (AI) into education has heralded a transformative era in the way students learn and faculties teach. Among the burgeoning array of AI tools, ChatGPT stands out as a versatile and powerful resource. Developed by OpenAI, ChatGPT is an AI-driven conversational model that generates human-like responses. This research draws on the Constructivism Learning Theory to uncover the key drivers pushing higher education students to use ChatGPT for academic purposes, and the mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…The ease with which AI can perform complex tasks might inadvertently encourage academic dishonesty, potentially undermining the educational ethics [23, 25]. Furthermore, the reliance on AI for academic tasks could trigger a decline in critical thinking and personal development skills among students, both of which are essential outcomes to enable the graduates in achieving economic, technological, and social advancements [26, 27].…”
Section: Introductionmentioning
confidence: 99%
“…The ease with which AI can perform complex tasks might inadvertently encourage academic dishonesty, potentially undermining the educational ethics [23, 25]. Furthermore, the reliance on AI for academic tasks could trigger a decline in critical thinking and personal development skills among students, both of which are essential outcomes to enable the graduates in achieving economic, technological, and social advancements [26, 27].…”
Section: Introductionmentioning
confidence: 99%
“…Since the inauguration of Chat Generative Pre-trained Transformer (ChatGPT) in 2022, there has been growing interest among students in using ChatGPT in education [ 1 ]. ChatGPT is a chatbot generated by the OpenAI, which assists users in creating human-like text by processing commands and conversations [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the use of ChatGPT in the context of higher education, see for example, refs. [ 1 , 2 , 3 , 4 ], have shown several benefits to using ChatGPT in education, such as receiving quick and prompt service, and academic and nonacademic support; developing language skills; and using editing services. Previous research has also shown that ChatGPT assists students in their assignments, projects, homework, and research tasks.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations